2001
DOI: 10.1007/s00428-001-0577-6
|View full text |Cite
|
Sign up to set email alerts
|

Preneoplastic non-papillary lesions and conditions of the urinary bladder: an update based on the Ancona International Consultation

Abstract: The result of the meeting is represented by a refined classification of the non-papillary intraepithelial lesions and conditions of the urothelium. This classification includes epithelial abnormalities (reactive urothelial atypia and flat urothelial hyperplasia), presumed preneoplastic lesions and conditions (keratinizing squamous and glandular metaplasia, and malignancy-associated cellular changes), as well as preneoplastic (dysplasia) and neoplastic non-invasive (carcinoma in situ) lesions. Each of these les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
5

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 55 publications
2
95
0
5
Order By: Relevance
“…Of these 70 cases, there were 24 (34%), which contained microinvasion. Of the patients with microinvasion, 5.8% had lymph node metas- 51 Further investigation is warranted to define the clinical significance of this diagnostic category.…”
Section: Microinvasive Carcinomamentioning
confidence: 99%
“…Of these 70 cases, there were 24 (34%), which contained microinvasion. Of the patients with microinvasion, 5.8% had lymph node metas- 51 Further investigation is warranted to define the clinical significance of this diagnostic category.…”
Section: Microinvasive Carcinomamentioning
confidence: 99%
“…Our finding of epimutations in normal appearing mucosa and concordant tumor samples supports the idea that the entire epithelium may be predisposed to premalignant change. 55 Tumor contamination of normal samples is possible but unlikely since these samples were carefully microdissected. Although not statistically significant, our findings do suggest a role for field cancerization through epigenetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated increasing incidence if associated with Cis or papillary carcinoma, but we lack recent studies concerning prognosis of isolated lesions (1,24). One reason for the lack of data might be the problem of reproducibility in grading dysplasia (12,13,25,26).…”
Section: Low Grade Urothelial Dysplasia (Lgud)mentioning
confidence: 98%
“…FUH was mostly seen in cases of follow-up of pTa tumors and generally considered as a minor finding. Several studies could demonstrate genetic abnormalities already present in hyperplasia such as loss of heterozygosity of FGFR-3 gene and deletion of chromosome 9 in 70% of FUH (10)(11)(12). This raises the question of whether FUH should be considered as detection of an early premalignant urothelium lesion with low-risk profile (13).…”
Section: Flat Urothelial Hyperplasia (Fuh)mentioning
confidence: 99%
See 1 more Smart Citation